2001
DOI: 10.1002/pds.621
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine use in patients hospitalized in a department of internal medicine: frequency and clinical correlates

Abstract: Prevalence of BZD use appeared to be fairly high among hospitalized patients. There were very few new BZD users during hospital stay, most of whom were stopped at discharge. Most treatments were started before hospital, and continued during and after hospital stay without clear reevaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
1
12
3
Order By: Relevance
“…Studies from other parts of the world show that prevalence rates vary hugely ranging from 7.5% currently taking a BDZ in French general population[15], 9.6% past month use in Lebanese general population[19], 19.1% taking BDZ regularly (one or more doses per week) at the time of admission to a Sydney teaching hospital[10], 33% taking BDZ at the time of admission to an Internal Medicine unit in France[12], 41.4% prescribed BDZ to medical/surgical inpatients in USA[9], and 86% lifetime prevalence of BDZ use in patients admitted to a Swiss psychiatric hospital[8]. The 45% point prevalence of BDZ use in psychiatric outpatients found in our study seems to be higher than the prevalence found in previous studies from Pakistan, and closer to the prevalence in inpatient units in international studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other parts of the world show that prevalence rates vary hugely ranging from 7.5% currently taking a BDZ in French general population[15], 9.6% past month use in Lebanese general population[19], 19.1% taking BDZ regularly (one or more doses per week) at the time of admission to a Sydney teaching hospital[10], 33% taking BDZ at the time of admission to an Internal Medicine unit in France[12], 41.4% prescribed BDZ to medical/surgical inpatients in USA[9], and 86% lifetime prevalence of BDZ use in patients admitted to a Swiss psychiatric hospital[8]. The 45% point prevalence of BDZ use in psychiatric outpatients found in our study seems to be higher than the prevalence found in previous studies from Pakistan, and closer to the prevalence in inpatient units in international studies.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller, single-center studies have found benzodiazepine initiation rates of 0-5.3%. [19][20][21][22][23] Our comparatively lower rate may be because of our selection criteria, our focus on the elderly (we observed a lower adjusted risk for the outcome in older cohorts), our strict outcome definition, the exclusion of long-term care residents, and the population-based use of administrative data for our analysis. What message do these results impart to clinicians?…”
Section: Discussionmentioning
confidence: 99%
“…Many patients are first introduced to benzodiazepines during hospitalization. [17][18][19][20][21][22][23] Short-term insomnia and consequent benzodiazepine initiation may result from a number of factors associated with hospitalization such as the effects of illness and new medications, environmental factors including noise and disruption of usual sleeping schedules, and anxiety. Although the intent of the benzodiazepine prescription may have been to manage the short period of time that the patient is in hospital, there are concerns that its initiation in this setting may result in chronic use after discharge, together with its accompanying risks.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between bed days and benzodiazepine prescription has been studied in several Western countries, the number of subjects was relatively small (<1,000) [ 12 - 16 ], the analysis was limited to the elderly [ 12 , 13 , 17 ] or to those at limited departments [ 12 , 14 , 15 ], or the diagnostic information was not controlled for in the analyses [ 4 , 18 ]. The findings are inconsistent among such Western studies, and no empirical study has been conducted on these issues in Japanese hospitals.…”
Section: Introductionmentioning
confidence: 99%